Accounting Students in the Role of Equal-Status Team Teacher for the Purpose of Knowledge and Competency Development - Marchantia Pollock; Stephen A. Coetzee; Astrid Schmulian (MDPI AG, 2023)
This study investigates the impact of engaging accounting students in a team-teaching role on their knowledge and competency development in a higher education setting. The research quantifies the knowledge gains from this learning-by-team-teaching intervention and explores students' experiences with this intervention through survey data. The findings suggest that engaging students in a team-teaching role, specifically a sequential equal-status team-teaching role incorporating interactive teaching styles, significantly enhances knowledge development, particularly among lower-performing students. Students reported a largely positive experience across all performance levels, attributing their growth to improved knowledge, teamwork, and communication skills provided by the intervention. The study recognizes the benefits derived from the team-based design of the intervention, such as enhanced social constructivist knowledge development. Overall, this study contributes to the existing body of knowledge on learning-by-teaching strategies. It emphasizes the potential of engaging students in a team-teaching role to enhance their academic performance and the development of key professional competencies.